Kejadian stunting ditinjau dari sosial demografi dan konsumsi ikan pada balita - Febry, Fatmalina; Ainy, Asmaripa; Sunarsih, Elvi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2025)
A review of the socio-demographic characteristics and children fish consumption on stunting incidenceBackground: Social demographics and protein intake are widely known to be related to stunting incidence. Fish, a source of complete and high-quality protein, contains essential amino acids and high digestibility protein so the body can absorb high amounts of protein. Fish contains nutrients that are very important for the growth and development of toddlers.Objective: This research aims to determine the socio-demographic characteristics and consumption of fish and its processed products related to the stunting incidence in children aged 12-59 months. Methods: This cross-sectional study was conducted from August to September 2022 at three health centers in Palembang City. A total of 120 toddlers aged 12-59 months, with 51.7% male and 48.3% female, were selected by purposive sampling. The variables of this study were toddler characteristics (age, gender, and nutritional status), family characteristics (mother's education, mother's occupation, number of family members, and family income), family fish consumption (type of fish product, portion size, frequency of fish consumption). The study was conducted by interviews using a questionnaire and anthropometric measurements of toddlers. Data were analyzed using the Chi-Square test with a 95% confidence interval and p<0.05 significance level. Results: Lower education of mothers, working mothers, large families, high family incomes, consuming processed fish with less large portions, and often consuming fish had a higher percentage of stunting incidence. On the other hand, it was found that all variables were not significantly correlated to stunting in toddlers.Conclusions: This study showed that socio-demographic variables and fish consumption were not significantly associated with stunting in children under five.